A Comparison of the Innate and Adaptive Immune Systems in Cartilaginous Fish, Ray-Finned Fish, and Lobe-Finned Fish - Smith, Nicole C.; Rise, Matthew L.; Christian, Sherri L. (Frontiers in Immunology, 2019)
The immune system is composed of two subsystems – the innate immune system and the adaptive immune system. The innate immune system is the first to respond to pathogens and does not retain memory of previous responses. Innate immune responses are evolutionarily older than adaptive responses and elements of innate immunity can be found in all multicellular organisms. If a pathogen persists, the adaptive immune system will engage the pathogen with specificity and memory. Several components of the adaptive system including immunoglobulins (Igs), T cell receptors (TCR) and major histocompatibility complex (MHC), are assumed to have arisen in the first jawed vertebrates – the Gnathostomata. This review will discuss and compare components of both the innate and adaptive immune systems in Gnathostomes, particularly in Chondrichthyes (cartilaginous fish) and in Osteichthyes (bony fish: the Actinopterygii (ray-finned fish) and the Sarcopterygii (lobe-finned fish)). While many elements of both the innate and adaptive immune systems are conserved within these species and with higher level vertebrates, some elements have marked differences. Components of the innate immune system covered here include physical barriers, such as the skin and gastrointestinal tract, cellular components, such as pattern recognition receptors and immune cells including macrophages and neutrophils, and humoral components, such as the complement system. Components of the adaptive system covered include the fundamental cells and molecules of adaptive immunity: B lymphocytes (B cells), T lymphocytes (T cells), immunoglobulins (Ig) and major histocompatibility complex (MHC). Comparative studies in fish such as those discussed here are essential for developing a comprehensive understanding of the evolution of the immune system.